Performance Evaluating of Honeyword Generation Methods: Traditional versus AI - Alkazzaz, Shahad Abdulkhalik; Mohammed, Saja Jasim (Sistemasi: Jurnal Sistem Informasi, 2025)
As the number of people using computers has increased, the risks to digital systems have increased too. That has necessitated the development of new techniques to defend against hackers. Authentication systems based on text passwords are an example of digital systems that face risks through internet use. Therefore, it was necessary to provide security and reliability to users while protecting their passwords. In the authentication database, A technique known as honeywords was used. In the digital world, honeywords are a popular technique used to enhance the security of users' actual passwords and are an additional strong layer of security. The benefit of this technique is its ability to detect unauthorized access attempts to the systems. In this paper, three of the most popular techniques for honeyword generation and other well-known intelligence algorithms are put in comparison using some evaluation metrics to study the performance of each one. The results illustrate a contrast in the performance of different techniques and intelligence algorithms based on the Hamming distance value.